Foreign articles as growth factor of falsification for scientific publications and reduction of scientometric indicators of organizations - Pototskaya O.Yu.; Lievykh A.E.; Mamchur V.I. (Medičnì Perspektivi)
Some orders of Ministry of Education and Science of Ukraine encourage scientific authors to publish their articles abroad but do not detail selection criteria of the journals recommended. As a result, authors choose the easiest way and publish their papers in low-quality foreign journals. Moreover, some false journals have been created since the Orders entered into force. In this article we emphasize the importance of journal registration in scientometric databases for the international and regional rating of universities. Also attention is paid to the need of verification of journal quality and its reliability by the authors before sending manuscripts for publication. To resolve these problems we propose to indicate URL link of the article in the annual scientific report of scientists, departments and organizations. It will help to verify the quality of the journal and concentrate attention of the authors on checking the existence of journal’s web site before sending their manuscripts. It is important to emphasize that journals without web sites do not influence on the rating of scientific organizations in any scientometric databases. If such link is absent, article should not be scored up for the rating. Additional way is to create adequate system of scientific ratings. For example, articles published in major scientometric databases, such as Scopus and Web of Science, should be scored two (or more) times higher than any other articles. Papers published in other scientometric databases (such as RISC) also should be scored higher than onother articles. Information about principal scientometric databases should be clarified for scientists to help them in choosing optimal journal for manuscripts publishing.